Repérer et caractériser les dynamiques urbaines : l’appui nouveau des humanités numériques - Iris Eshkol-Taravella; Jade Mekki; Olivier Ratouis; Alain Guez; Rémi Simon (Humanités Numériques)
This article presents the work of urban corpus creation and processing, i.e. the methodology adopted, the choices made, the problems encountered and the results obtained at these two stages. It shows the work made in the context of the Vital project (Ville et traitement automatique des langues, “natural language processing and the city”), which draws from the digital humanities and brings together researchers in natural language processing (NLP), architects and urban planners in an original and innovative way. The aim of this multi-disciplinary research is to analyse the understanding of space as dynamic, using recent advances in the field of NLP.